End game the end of the debt supercycle and how it changes everything - Mauldin, John (John Wiley & Sons, 2011)
"An exhaustive look at world markets and why the economy has been so unpredictable Greece isn't the only country drowning in debt. The Debt Supercycle?when the easily managed, decades-long growth of debt results in a massive sovereign debt and credit crisis?is affecting developed countries around the world, including the United States. For these countries, there are only two options, and neither is good?restructure the debt or reduce it through austerity measures. The End Game details the Debt Supercycle and the sovereign debt crisis, and shows that, while there are no good choices, the worst choice would be to ignore the deleveraging resulting from the credit crisis. Reveals why the world economy is in for an extended period of sluggish growth, high unemployment, and volatile markets punctuated by persistent recessions Reviews global markets, trends in population, government policies, and currencies Other titles by Mauldin: Bull's Eye Investing: Targeting Real Returns in a Smoke and Mirrors Market, also by Wiley Around the world, countries are faced with difficult choices. The End Game provides a framework for making those choices."--